Sosialisasi Program Simpan Pinjam Khusus Perempuan Untuk Peningkatan Perekonomian Masyarakat di Desa Marjandi Pematang - Syafruddin Ritonga; Nina Salmaniah Siregar; Taufik Wal Hidayat; Armansyah Matondang (Pelita Masyarakat, 2021)
The purpose of this socialization is to provide knowledge to mothers about savings and loans, especially women who have a more role and benefit for the welfare and economy of the family. The method used is direct socialization to mothers, in the village of Marjandi Pematang Siantar. From the results of this dedication, that with the SPP mothers can play a role in increasing household income / income so that the economy can be further improved. SPP can help the capital of poor families if they want to open a business so that it is hoped that the community can live in prosperity. the people's economy can be more stable for those who really use it properly and correctly, namely as business capital. Members in a group co-exist and help each other, equally bear if one member does not pay then the other is responsible for the payment.